1989
DOI: 10.3109/02713688909013903
|View full text |Cite
|
Sign up to set email alerts
|

Focal irradiation of perforating eye injuries

Abstract: Plaques constructed with 125I were used to irradiate the sites of perforating ocular injuries in rabbits. An approximate dose of 16Gy given over a period of 6 days was shown to significantly reduce intraocular cellular proliferation when irradiation was commenced within 24 hours after injury. If irradiation was delayed until day 5, this reduction in cellular proliferation and intraocular membrane formation did not occur. Smaller radiation doses of approximately 6Gy given within 24 hours post-injury and adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…[33][34][35][36][37] These effects of radiation are both dose and dose rate dependent. 38 Irradiation of a macula containing classic or occult subretinal neovascularisation can directly affect angiogenesis by destroying neovascular endothelial cells and cytokine producing macrophages, or alter the regulatory genes which produce endothelial growth regulating cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35][36][37] These effects of radiation are both dose and dose rate dependent. 38 Irradiation of a macula containing classic or occult subretinal neovascularisation can directly affect angiogenesis by destroying neovascular endothelial cells and cytokine producing macrophages, or alter the regulatory genes which produce endothelial growth regulating cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…It is during the period of maximum cellular proliferation in the neovascularization process that endothelial cells are most sensitive to irradiation [6,10]. In contrast, mature, nonproliferating retinal and choroidal vessels are more radioresistant, and the risk of development of radiation-related retinopathy is low at doses of less than 25-30 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Chakravarthy et al [9,11] found that a dose of 16 Gy applied with a plaque containing radioactive 125 I seeds was most effective to inhibit intraocular membrane formation. The same authors evaluated irradiated and nonirradiated vitreoretinal membranes obtained from rabbit eyes in vitro [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Chakravarthy et al [9,11] had used a cobalt applicator and delivered a dose of 100 Gy to the sclera and 80 Gy to the retina and choroid and found that while 19 of 24 nonirradiated rabbit eyes developed vitreoretinal membranes, only 4 of 24 irradiated eyes developed such membranes. In another study, Chakravarthy et al [9,11] found that a dose of 16 Gy applied with a plaque containing radioactive 125 I seeds was most effective to inhibit intraocular membrane formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation